Increasing E-learning Modalities through Creative Use of Technology in the Post-Pandemic Era - Thirumeni Subramaniam,; Md Rosli Ismail, (IntechOpen, 2023)
The post-Pandemic Era leaves us with the question of whether to pursue the move toward digital education or step back into face-to-face education. The reasons for the debate can vary from the lack of infrastructure to stringent national qualification agencies. Regardless, the pandemic has taught us to be adaptable. As such, progress must be made in both formats, digital and conventional education. In moving e-learning forward while coping with diverse needs of global education across geographical, age, ethnicity, and socioeconomic boundaries, the inclusion of read, watch, and listen (RWL) modalities becomes essential. Successful deliveries of different modalities lie in creativity and creative use of technology that is driven by the achievement of targeted learning outcomes. This chapter attempts to discuss the experience of creating RWL modalities by embracing the universal design, and other creative use of technology to develop twenty-first century learners. (Abstract by authors)